Seasonal variations of schizophrenic patients in emergency departments in Sofia, Bulgaria - Spasova, Zornitsa (South Eastern European Journal of Public Health (SEEJPH), 2015)
Aim: The purpose of this study was to reveal the seasonal distribution of emergency department visits of schizophrenic patients in Sofia, Bulgaria. Methods: We collected daily data for visits of patients with schizophrenia, schizotypal and delusional disorders in the emergency center of the regional dispenser for mental disorders in the city of Sofia for the period 1998-2003. The total number of emergency visits was 5723 (mean daily visits: 5.04±2.4). T-test was used to compare the monthly and seasonal distribution of visits. Results: The season with the highest levels of emergency visits was summer, and the lowest levels were observed in winter (P<0.0001). Spring and autumn had intermediate values close to the mean value, and significantly differentiated from winter values. The month with the highest admission rates was September, followed by May and the three summer’s months. The lowest levels were observed in December, October and January, with statistically significant differences observed between the values of all the three months. Differences between July values compared with December and October values were significant, but not with January values. Conclusion: The study showed significant seasonal and monthly differences in emergency schizophrenics’ visits. The data confirm the outcome of similar studies conducted in countries with temperate climate in the Northern Hemisphere. These results could prove useful for psychiatrists, public health specialists, and governmental authorities dealing with team planning and prevention programs in the field of psychiatry.